Characterization of functional P2X1 receptors in mouse megakaryocytes - Ikeda, Masahiro (Thrombosis Research, 2007)
Abstract Introduction Although accumulating evidence within the past 5 years strongly supports the importance of platelet P2X1 receptors in hemostasis and thrombosis, P2X1 receptors of platelet and/or its progenitor cell, megakaryocyte, have not been fully characterized. The aim of this study was to electrophysiologically and pharmacologically characterize the functional P2X1 receptors on mouse megakaryocytes. Materials and methods The currents in response to nucleotides were examined using the patch-clamp whole-cell recording. Results The agonist profile of megakaryocyte P2X1 receptors was ATP > α,β-methylene ATP > β,γ-methylene ATP. The P2X1 receptors exhibited substantial monovalent as well as divalent cation permeability and the ratios of Na+ to Cs+ and Ca2+ to Cs+ permeability were 1 and 2.5, respectively. P2X receptor antagonists except suramin significantly inhibited the P2X1 responses with an IC50 values of 0.4 μM for pyridoxal-phosphate-6-azophenyl-2′,4′-disulfonate (PPADS), 0.3 μM for 2′,3′- O -(2,4,6-trinitophenyl)-adenosine 5′-triphosphate (TNP-ATP), 20 μM for reactive blue 2 (RB2), or 160 μM for 8,8′-(carbonylbis(imino-3,1-phenylene carbonylimino)bis(1,3,5-naphthalenetrisulfonic acid) (NF023), respectively. Suramin had no significant effect on the P2X1 responses. In rat megakaryocytes, suramin similarly had no significant effect on the P2X1 responses, but abolished the P2Y receptor-mediated responses, indicating that the suramin was active under present experimental condition. Conclusions These results provide the basic properties of mouse megakaryocyte P2X1 receptors and would be helpful to examine the P2 receptor signaling in platelets and megakaryocytes.